Alterations of Amino Acids and Monoamine Metabolism in Male Fmr1 Knockout Mice: A Putative Animal Model of the Human Fragile X Mental Retardation Syndrome - Michael Gruss; Katharina Braun (Neural Plasticity)
The Fragile X syndrome, a common form of mental retardation in humans, is caused by silencing the fragile X mental retardation (FMR1) geneleading to the absence of the encoded fragile X mental retardation protein 1 (FMRP). We describe morphological and behavioral abnormalities for both affected humans and Fmr1 knockout mice, a putative animal model for the human Fragile X syndrome. The aim of the present study was to identify possible neurochemical abnormalities in Fmr1 knockout mice, with particular focus on neurotransmission. Significant region-specific differences: of basal neurotransmitter and metabolite levels were found between wildtype and Fmr1 knockout animals, predominantly in juveniles (post-natal days 28 to 31). Adults (postnatal days 209 to 221) showed only few abnormalities as compared with the wildtype. In juvenile knockout mice, aspartate and taurine were especially increased in cortical regions, striatum, hippocampus, cerebellum, and brainstem. In addition, juveniles showed an altered balance between excitatory and inhibitory amino acids in the caudal cortex, hippocampus, and brainstem. We detected very few differences in monoamine turnover in both age stages. The results presented here provide the first evidence that lack of FMRP expression in FMRP knockout mice is accompanied by age-dependent, region-specific alterations in neurotransmission.